2018
DOI: 10.3390/su10040971
|View full text |Cite
|
Sign up to set email alerts
|

Physical Forcing-Driven Productivity and Sediment Flux to the Deep Basin of Northern South China Sea: A Decadal Time Series Study

Abstract: Abstract:Understanding the driving forces of absorption of anthropogenic CO 2 by the oceans is critical for a sustainable ocean carbon cycle. Decadal sinking particle flux data collected at 1000 m, 2000 m, and 3500 m at the South East Asia Time Series Study (SEATS) Station (18 • N, 116 • E), which was located in the northern South China Sea (nSCS), show that the fluxes undergo strong seasonal and interannual variability. Changes in the flux data are correlated with the satellite-derived chlorophyll-a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…At SM18, the S max and its corresponding temperature showed the same result, where a gradual increase in DO min corresponded to a gradual increase in the WPS seawater proportions in 2003-2004, and vice versa in 2005-2011 ( Figure 8B). Lui et al (2018) showed that, similar to that in 2003-2004, there was a strong interannual WPS seawater intrusion between 2014 and 2016 ( Figure 8C). Consequently, the SSS at SEATS gradually increased from 33.19 in 2013/9 to the third highest of 34.46 in 2016/1 (Figure 4B).…”
Section: Offshore Seawater Intrusion Increases Do But Reduces Nutriensupporting
confidence: 65%
See 3 more Smart Citations
“…At SM18, the S max and its corresponding temperature showed the same result, where a gradual increase in DO min corresponded to a gradual increase in the WPS seawater proportions in 2003-2004, and vice versa in 2005-2011 ( Figure 8B). Lui et al (2018) showed that, similar to that in 2003-2004, there was a strong interannual WPS seawater intrusion between 2014 and 2016 ( Figure 8C). Consequently, the SSS at SEATS gradually increased from 33.19 in 2013/9 to the third highest of 34.46 in 2016/1 (Figure 4B).…”
Section: Offshore Seawater Intrusion Increases Do But Reduces Nutriensupporting
confidence: 65%
“…Indeed, the potential temperature (θ) vs. salinity plot provides information on such proportions. We differentiated the WPS and SCS seawaters using θ and salinity, as the WPS and SCS seawaters have distinctive θ and salinity distributions from the surface to the bottom (Chen et al, 2016;Lui et al, 2018). Generally speaking, the surface and subsurface waters of the WPS are notably saltier than that of the SCS.…”
Section: Offshore Seawater Intrusion Increases Do But Reduces Nutrienmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of the marine organic carbon cycle in a changing climate has been discussed by several papers in this issue [64][65][66][67]; the dynamics of which are related to temporal (seasonal, inter-annual) variations in hydrodynamics, nutrient cycling, and other biogeochemical processes. Continuous monitoring efforts and modelling studies are essential in predicting future changes organic carbon distributions with respect to identified factors.…”
Section: Organic Carbon and The Sustainable Use Of The Environment Anmentioning
confidence: 99%